Neurogenic differentiation by hippocampal neural stem and progenitor cells is biased by NFIX expression - Harris, L.; Zalucki, O.; Clément, O.; Fraser, J.; Matuzelski, E.; Oishi, S.; Harvey, T.; Burne, T.; Heng, Julian; Gronostajski, R.; Piper, M. (Company of Biologists LTD, 2018)
© 2018. Published by The Company of Biologists Ltd. Our understanding of the transcriptional programme underpinning adult hippocampal neurogenesis is incomplete. In mice, under basal conditions, adult hippocampal neural stem cells (AH-NSCs) generate neurons and astrocytes, but not oligodendrocytes. The factors limiting oligodendrocyte production, however, remain unclear. Here, we reveal that the transcription factor NFIX plays a key role in this process. NFIX is expressed by AH-NSCs, and its expression is sharply upregulated in adult hippocampal neuroblasts. Conditional ablation of Nfix from AH-NSCs, coupled with lineage tracing, transcriptomic sequencing and behavioural studies collectively reveal that NFIX is cell-autonomously required for neuroblast maturation and survival. Moreover, a small number of AH-NSCs also develop into oligodendrocytes following Nfix deletion. Remarkably, when Nfix is deleted specifically from intermediate progenitor cells and neuroblasts using a Dcx-creERT2driver, these cells also display elevated signatures of oligodendrocyte gene expression. Together, these results demonstrate the central role played by NFIX in neuroblasts within the adult hippocampal stem cell neurogenic niche in promoting the maturation and survival of these cells, while concomitantly repressing oligodendrocyte gene expression signatures.